You are on page 1of 11

Nonhomogeneous Linear Equations

In this section we learn how to solve second-order nonhomogeneous linear differential equations with constant coefficients, that is, equations of the form
1

ay  by  cy  Gx

where a, b, and c are constants and G is a continuous function. The related homogeneous
equation
2

ay  by  cy  0

is called the complementary equation and plays an important role in the solution of the
original nonhomogeneous equation (1).
3 Theorem The general solution of the nonhomogeneous differential equation (1)
can be written as

yx  ypx  ycx

where yp is a particular solution of Equation 1 and yc is the general solution of the
complementary Equation 2.
Proof All we have to do is verify that if y is any solution of Equation 1, then y  yp is a
solution of the complementary Equation 2. Indeed

ay  yp   by  yp   cy  yp   ay  ayp  by  byp  cy  cyp

 ay  by  cy  ayp  byp  cyp 
 tx  tx  0
We know from Additional Topics: Second-Order Linear Differential Equations how to
solve the complementary equation. (Recall that the solution is yc  c1 y1  c2 y2 , where y1
and y2 are linearly independent solutions of Equation 2.) Therefore, Theorem 3 says that
we know the general solution of the nonhomogeneous equation as soon as we know a particular solution yp . There are two methods for finding a particular solution: The method of
undetermined coefficients is straightforward but works only for a restricted class of functions G. The method of variation of parameters works for every function G but i0s usually
more difficult to apply in practice.
The Method of Undetermined Coefficients
We first illustrate the method of undetermined coefficients for the equation
ay  by  cy  Gx
where Gx) is a polynomial. It is reasonable to guess that there is a particular solution
yp that is a polynomial of the same degree as G because if y is a polynomial, then
ay  by  cy is also a polynomial. We therefore substitute ypx  a polynomial (of the
same degree as G ) into the differential equation and determine the coefficients.
EXAMPLE 1 Solve the equation y  y  2y  x 2.
SOLUTION The auxiliary equation of y  y  2y  0 is

r 2  r  2  r  1r  2  0
1

with roots r  1, 2. So the solution of the complementary equation is

yc  c1 e x  c2 e2x
Since Gx  x 2 is a polynomial of degree 2, we seek a particular solution of the form
ypx  Ax 2  Bx  C
Then yp  2Ax  B and yp  2A so, substituting into the given differential equation, we
have
2A  2Ax  B  2Ax 2  Bx  C  x 2
or

Polynomials are equal when their coefficients are equal. Thus

Figure 1 shows four solutions of the differential equation in Example 1 in terms of the particular solution yp and the functions f x  e x
and tx  e2 x.

2A  2B  0

2A  B  2C  0

A   12

yp+2f+3g
yp+3g

2A  1

B   12

C   34

A particular solution is therefore

yp+2f

_3

ypx   12 x 2  12 x  34

yp

and, by Theorem 3, the general solution is

_5

y  yc  yp  c1 e x  c2 e2x  12 x 2  12 x  34

FIGURE 1

If Gx (the right side of Equation 1) is of the form Ce k x, where C and k are constants,
then we take as a trial solution a function of the same form, ypx  Ae k x, because the
derivatives of e k x are constant multiples of e k x.
EXAMPLE 2 Solve y  4y  e 3x.
SOLUTION The auxiliary equation is r 2  4  0 with roots 2i, so the solution of the
Figure 2 shows solutions of the differential
equation in Example 2 in terms of yp and the
functions f x  cos 2x and tx  sin 2x.
Notice that all solutions approach  as x l 
and all solutions resemble sine functions when
x is negative.

complementary equation is
ycx  c1 cos 2x  c2 sin 2x
For a particular solution we try ypx  Ae 3x. Then yp  3Ae 3x and yp  9Ae 3x. Substituting into the differential equation, we have
9Ae 3x  4Ae 3x   e 3x

yp+f+g

yp+g
yp

_4
yp+f
_2

FIGURE 2

so 13Ae 3x  e 3x and A  131 . Thus, a particular solution is

2

ypx  131 e 3x
and the general solution is
yx  c1 cos 2x  c2 sin 2x  131 e 3x
If Gx is either C cos kx or C sin kx, then, because of the rules for differentiating the
sine and cosine functions, we take as a trial particular solution a function of the form
ypx  A cos kx  B sin kx

EXAMPLE 3 Solve y  y  2y  sin x.

SOLUTION We try a particular solution

ypx  A cos x  B sin x

yp  A sin x  B cos x

Then

so substitution in the differential equation gives

A cos x  B sin x  A sin x  B cos x  2A cos x  B sin x  sin x
3A  B cos x  A  3B sin x  sin x

or
This is true if
3A  B  0

and

A  3B  1

The solution of this system is

A   101

B   103

so a particular solution is
ypx   101 cos x  103 sin x
In Example 1 we determined that the solution of the complementary equation is
yc  c1 e x  c2 e2x. Thus, the general solution of the given equation is
yx  c1 e x  c2 e2x  101 cos x  3 sin x
If Gx is a product of functions of the preceding types, then we take the trial solution to be a product of functions of the same type. For instance, in solving the differential
equation
y  2y  4y  x cos 3x
we would try
ypx  Ax  B cos 3x  Cx  D sin 3x
If Gx is a sum of functions of these types, we use the easily verified principle of superposition, which says that if yp1 and yp2 are solutions of
ay  by  cy  G1x

respectively, then yp1  yp2 is a solution of

ay  by  cy  G1x  G2x
EXAMPLE 4 Solve y  4y  xe x  cos 2x.
SOLUTION The auxiliary equation is r 2  4  0 with roots 2, so the solution of the com-

plementary equation is ycx  c1 e 2x  c2 e2x. For the equation y  4y  xe x we try

yp1x  Ax  Be x
Then yp1  Ax  A  Be x, yp1  Ax  2A  Be x, so substitution in the equation
gives
Ax  2A  Be x  4Ax  Be x  xe x
or

3Ax  2A  3Be x  xe x

Thus, 3A  1 and 2A  3B  0, so A   13 , B   29 , and

yp1x  ( 13 x  29 )e x
For the equation y  4y  cos 2x, we try
yp2x  C cos 2x  D sin 2x
In Figure 3 we show the particular solution
yp  yp1  yp 2 of the differential equation in
Example 4. The other solutions are given in
terms of f x  e 2 x and tx  e2 x.

Substitution gives
4C cos 2x  4D sin 2x  4C cos 2x  D sin 2x  cos 2x
8C cos 2x  8D sin 2x  cos 2x

or

yp+2f+g

Therefore, 8C  1, 8D  0, and

yp+g
yp+f
_4

yp2x   18 cos 2x

yp

_2

y  yc  yp1  yp2  c1 e 2x  c2 e2x  ( 13 x  29 )e x  18 cos 2x

FIGURE 3

Finally we note that the recommended trial solution yp sometimes turns out to be a solution of the complementary equation and therefore cant be a solution of the nonhomogeneous equation. In such cases we multiply the recommended trial solution by x (or by x 2
if necessary) so that no term in ypx is a solution of the complementary equation.
EXAMPLE 5 Solve y  y  sin x.
SOLUTION The auxiliary equation is r 2  1  0 with roots i, so the solution of the com-

plementary equation is
ycx  c1 cos x  c2 sin x
Ordinarily, we would use the trial solution
ypx  A cos x  B sin x
but we observe that it is a solution of the complementary equation, so instead we try
ypx  Ax cos x  Bx sin x
Then

ypx  A cos x  Ax sin x  B sin x  Bx cos x

ypx  2A sin x  Ax cos x  2B cos x  Bx sin x

The graphs of four solutions of the differential equation in Example 5 are shown in Figure 4.

yp  yp  2A sin x  2B cos x  sin x

so A   12 , B  0, and

_2

ypx   12 x cos x

yp
_4

FIGURE 4

The general solution is

yx  c1 cos x  c2 sin x  12 x cos x

We summarize the method of undetermined coefficients as follows:

1. If Gx  e kxPx, where P is a polynomial of degree n, then try ypx  e kxQx,

where Qx is an nth-degree polynomial (whose coefficients are determined by

substituting in the differential equation.)
2. If Gx  e kxPx cos mx or Gx  e kxPx sin mx, where P is an nth-degree

polynomial, then try

ypx  e kxQx cos mx  e kxRx sin mx
where Q and R are nth-degree polynomials.
Modification: If any term of yp is a solution of the complementary equation, multiply yp
by x (or by x 2 if necessary).
EXAMPLE 6 Determine the form of the trial solution for the differential equation

y  4y  13y  e 2x cos 3x.

SOLUTION Here Gx has the form of part 2 of the summary, where k  2, m  3, and

Px  1. So, at first glance, the form of the trial solution would be
ypx  e 2xA cos 3x  B sin 3x

But the auxiliary equation is r 2  4r  13  0, with roots r  2  3i, so the solution

of the complementary equation is
ycx  e 2xc1 cos 3x  c2 sin 3x
This means that we have to multiply the suggested trial solution by x. So, instead, we
use
ypx  xe 2xA cos 3x  B sin 3x

The Method of Variation of Parameters

Suppose we have already solved the homogeneous equation ay  by  cy  0 and written the solution as
4

yx  c1 y1x  c2 y2x

where y1 and y2 are linearly independent solutions. Lets replace the constants (or parameters) c1 and c2 in Equation 4 by arbitrary functions u1x and u2x. We look for a particular solution of the nonhomogeneous equation ay  by  cy  Gx of the form
5

ypx  u1xy1x  u2xy2x

(This method is called variation of parameters because we have varied the parameters c1
and c2 to make them functions.) Differentiating Equation 5, we get
6

yp  u1 y1  u2 y2   u1 y1  u2 y2 

Since u1 and u2 are arbitrary functions, we can impose two conditions on them. One condition is that yp is a solution of the differential equation; we can choose the other condition
so as to simplify our calculations. In view of the expression in Equation 6, lets impose the
condition that
7

u1 y1  u2 y2  0

Then

Substituting in the differential equation, we get

au1 y1  u2 y2  u1 y1  u2 y2  bu1 y1  u2 y2   cu1 y1  u2 y2   G
or
8

u1ay1  by1  cy1   u2ay2  by2  cy2   au1 y1  u2 y2   G

But y1 and y2 are solutions of the complementary equation, so

ay1  by1  cy1  0

and

and Equation 8 simplifies to

au1 y1  u2 y2   G

Equations 7 and 9 form a system of two equations in the unknown functions u1 and u2 .
After solving this system we may be able to integrate to find u1 and u2 and then the particular solution is given by Equation 5.
EXAMPLE 7 Solve the equation y  y  tan x, 0  x   2.
SOLUTION The auxiliary equation is r 2  1  0 with roots i, so the solution of

y  y  0 is c1 sin x  c2 cos x. Using variation of parameters, we seek a solution

of the form
ypx  u1x sin x  u2x cos x
Then

yp  u1 sin x  u2 cos x  u1 cos x  u2 sin x

Set
u1 sin x  u2 cos x  0

10

Then

For yp to be a solution we must have

yp  yp  u1 cos x  u2 sin x  tan x

11

Solving Equations 10 and 11, we get

u1sin 2x  cos 2x  cos x tan x

Figure 5 shows four solutions of the

differential equation in Example 7.

u1  sin x

2.5

u1x  cos x

(We seek a particular solution, so we dont need a constant of integration here.) Then,
from Equation 10, we obtain
0
yp

u2  

sin x
sin 2x
cos 2x  1
u1  

 cos x  sec x
cos x
cos x
cos x

_1

FIGURE 5

So

(Note that sec x  tan x  0 for 0  x   2.) Therefore

ypx  cos x sin x  sin x  lnsec x  tan x cos x
 cos x lnsec x  tan x
and the general solution is
yx  c1 sin x  c2 cos x  cos x lnsec x  tan x

Exercises

17. y  2 y  10 y  x 2ex cos 3x

18. y  4y  e 3x  x sin 2x

110

Solve the differential equation or initial-value problem

using the method of undetermined coefficients.
1. y  3y  2y  x

2. y  9y  e

3. y  2y  sin 4x

7. y  y  e x  x 3,

y0  2,

8. y  4y  e x cos x,

y0  2,

y0  0

; 1112

Graph the particular solution and several other solutions.

What characteristics do these solutions have in common?

13 18

13. y  9 y  e

 x sin x
2

x

14. y  9 y  xe

cos  x

15. y  9 y  1  xe 9x

2328
Solve the differential equation using the method of variation of parameters.

1
1  ex

25. y  3y  2y 

Write a trial solution for the method of undetermined

coefficients. Do not determine the coefficients.
2x

11. 4y  5y  y  e x

22. y  y  e x

y0  1,

21. y  2y  y  e 2x

y0  2

y0  1

19. y  4y  x

y0  0

y0  1,

Solve the differential equation using (a) undetermined

coefficients and (b) variation of parameters.

6. y  2y  y  xex

5. y  4y  5y  e

1922

4. y  6y  9y  1  x
x

9. y  y  xe x,

3x

26. y  3y  2y  sine x 

27. y  y 

1
x
e2x
x3

28. y  4y  4y 

8 NONHOMOGENEOUS LINEAR EQUATIONS

S

1. y  c1 e2x  c2 ex  2 x 2  2 x 
1

3. y  c1  c2 e 2x 

7
4

cos 4x  201 sin 4x

1
5. y  e c1 cos x  c2 sin x  10 ex
3
11
1 x
7. y  2 cos x  2 sin x  2 e  x 3  6x
1
9. y  e x ( 2 x 2  x  2)
5
11.
The solutions are all
asymptotic to yp  e x10 as
x l . Except for yp ,
all solutions approach
_2
4
yp
either  or  as x l .
1
40

2x

_4

13.
15.
17.
19.
21.
23.
25.
27.

yp  Ae 2x  Bx 2  Cx  D cos x  Ex 2  Fx  G sin x

yp  Ax  Bx  C e 9x
yp  xex Ax 2  Bx  C  cos 3x  Dx 2  Ex  F sin 3x
y  c1 cos 2x  c2 sin 2x  14 x
y  c1e x  c2 xe x  e 2x
y  c1  x sin x  c2  ln cos x cos x
y  c1  ln1  ex e x  c2  ex  ln1  ex e 2x
y  [c1  12 x e xx dx]ex  [c2  12 x exx dx]e x

Solutions: Nonhomogeneous Linear Equations

1. The auxiliary equation is r 2 + 3r + 2 = (r + 2)(r + 1) = 0, so the complementary solution is
yc (x) = c1 e2x + c2 ex . We try the particular solution yp (x) = Ax2 + Bx + C, so yp0 = 2Ax + B and
yp00 = 2A. Substituting into the differential equation, we have (2A) + 3(2Ax + B) + 2(Ax2 + Bx + C) = x2 or
2Ax2 + (6A + 2B)x + (2A + 3B + 2C) = x2 . Comparing coefficients gives 2A = 1, 6A + 2B = 0, and
2A + 3B + 2C = 0, so A = 12 , B = 32 , and C =
2x

+ c2 e

1 2
x
2

7
.
4
3
x
2

Thus the general solution is

+ 74 .

3. The auxiliary equation is r 2 2r = r(r 2) = 0, so the complementary solution is yc (x) = c1 + c2 e2x . Try the
particular solution yp (x) = A cos 4x + B sin 4x, so yp0 = 4A sin 4x + 4B cos 4x

and yp00 = 16A cos 4x 16B sin 4x. Substitution into the differential equation
gives (16A cos 4x 16B sin 4x) 2(4A sin 4x + 4B cos 4x) = sin 4x

(16A 8B) cos 4x + (8A 16B) sin 4x = sin 4x. Then 16A 8B = 0 and 8A 16B = 1
1
and B = 20
. Thus the general solution is y(x) = yc (x) + yp (x) = c1 + c2 e2x +

1
40

cos 4x

1
20

A=

1
40

sin 4x.

5. The auxiliary equation is r 2 4r + 5 = 0 with roots r = 2 i, so the complementary solution is

yc (x) = e2x (c1 cos x + c2 sin x). Try yp (x) = Aex , so yp0 = Aex and yp00 = Aex . Substitution gives
Aex 4(Aex ) + 5(Aex ) = ex
2x

10Aex = ex

A=

1
.
10

1 x
e .
10

7. The auxiliary equation is r 2 + 1 = 0 with roots r = i, so the complementary solution is

yc (x) = c1 cos x + c2 sin x. For y00 + y = ex try yp1 (x) = Aex . Then yp0 1 = yp001 = Aex and substitution gives
Aex + Aex = ex

A = 12 , so yp1 (x) = 12 ex . For y00 + y = x3 try yp2 (x) = Ax3 + Bx2 + Cx + D.

Then yp0 2 = 3Ax2 + 2Bx + C and yp002 = 6Ax + 2B. Substituting, we have
6Ax + 2B + Ax3 + Bx2 + Cx + D = x3 , so A = 1, B = 0, 6A + C = 0 C = 6, and 2B + D = 0

D = 0. Thus yp2 (x) = x3 6x and the general solution is

y(x) = yc (x) + yp1 (x) + yp2 (x) = c1 cos x + c2 sin x + 12 ex + x3 6x. But 2 = y(0) = c1 +

and 0 = y0 (0) = c2 +
y(x) =

3
2

cos x +

11
2

1
2

c2 =

11
.
2

1
2

c1 =

3
2

Thus the solution to the initial-value problem is

sin x + 12 ex + x3 6x.

9. The auxiliary equation is r 2 r = 0 with roots r = 0, r = 1 so the complementary solution is yc (x) = c1 + c2 ex .

Try yp (x) = x(Ax + B)ex so that no term in yp is a solution of the complementary equation. Then

yp0 = (Ax2 + (2A + B)x + B)ex and yp00 = (Ax2 + (4A + B)x + (2A + 2B))ex . Substitution into the
differential equation gives (Ax2 + (4A + B)x + (2A + 2B))ex (Ax2 + (2A + B)x + B)ex = xex

(2Ax + (2A + B))ex = xex A = 12 , B = 1. Thus yp (x) = 12 x2 x ex and the general solution is

11. yc (x) = c1 ex/4 + c2 ex . Try yp (x) = Aex . Then

10Aex = ex , so A =

1
10

and the general solution is

y(x) = c1 ex/4 + c2 ex +

1 x
e .
10

of exponential curves and with the exception of the particular

solution (which approaches 0 as x ), they all approach
either or as x . As x , all solutions are
asymptotic to yp =

1 x
e .
10

13. Here yc (x) = c1 cos 3x + c2 sin 3x. For y00 + 9y = e2x try yp1 (x) = Ae2x and for y 00 + 9y = x2 sin x try
yp2 (x) = (Bx2 + Cx + D) cos x + (Ex2 + F x + G) sin x. Thus a trial solution is
yp (x) = yp1 (x) + yp2 (x) = Ae2x + (Bx2 + Cx + D) cos x + (Ex2 + F x + G) sin x.
15. Here yc (x) = c1 + c2 e9x . For y 00 + 9y0 = 1 try yp1 (x) = Ax (since y = A is a solution to the complementary
equation) and for y 00 + 9y0 = xe9x try yp2 (x) = (Bx + C)e9x .
17. Since yc (x) = ex (c1 cos 3x + c2 sin 3x) we try
yp (x) = x(Ax2 + Bx + C)ex cos 3x + x(Dx2 + Ex + F )ex sin 3x (so that no term of yp is a solution of the
complementary equation).
Note: Solving Equations (7) and (9) in The Method of Variation of Parameters gives

u01 =

Gy2
a (y1 y20 y2 y10 )

u02 =

and

Gy1
a (y1 y20 y2 y10 )

We will use these equations rather than resolving the system in each of the remaining exercises in this section.

19. (a) The complementary solution is yc (x) = c1 cos 2x + c2 sin 2x. A particular solution is of the form
yp (x) = Ax + B. Thus, 4Ax + 4B = x

A=

1
4

and B = 0 yp (x) = 14 x. Thus, the general

(b) In (a), yc (x) = c1 cos 2x + c2 sin 2x, so set y1 = cos 2x, y2 = sin 2x. Then
y1 y20 y2 y10 = 2 cos2 2x + 2 sin2 2x = 2 so u01 = 12 x sin 2x
R

R

yp (x) = 14 x cos 2x + 12 sin 2x cos 2x + 14 x sin 2x + 12 cos 2x sin 2x = 14 x. Thus

y(x) = yc (x) + yp (x) = c1 cos 2x + c2 sin 2x + 14 x.

r = 0, 1, so the complementary solution is yc (x) = c1 ex + c2 xex . A particular

solution is of the form yp (x) = Ae2x . Thus 4Ae2x 4Ae2x + Ae2x = e2x

2x

Ae2x = e2x
x

yp (x) = e . So a general solution is y(x) = yc (x) + yp (x) = c1 e + c2 xe + e2x .

A=1

(b) From (a), yc (x) = c1 ex + c2 xex , so set y1 = ex , y2 = xex . Then, y1 y20 y2 y10 = e2x (1 + x) xe2x = e2x
R
and so u01 = xex u1 (x) = xex dx = (x 1)ex [by parts] and u02 = ex
R
u2 (x) = ex dx = ex . Hence yp (x) = (1 x)e2x + xe2x = e2x and the general solution is
y(x) = yc (x) + yp (x) = c1 ex + c2 xex + e2x .

23. As in Example 6, yc (x) = c1 sin x + c2 cos x, so set y1 = sin x, y2 = cos x. Then

sec x cos x
y1 y20 y2 y10 = sin2 x cos2 x = 1, so u01 =
= 1 u1 (x) = x and
1
R
sec x sin x
u02 =
= tan x u2 (x) = tan xdx = ln |cos x| = ln(cos x) on 0 < x < 2 . Hence
1
yp (x) = x sin x + cos x ln(cos x) and the general solution is y(x) = (c1 + x) sin x + [c2 + ln(cos x)] cos x.
25. y1 = ex , y2 = e2x and y1 y20 y2 y10 = e3x . So u01 =
Z

e2x
ex
=
and
x
3x
(1 + e )e
1 + ex

ex
ex
ex
dx = ln(1 + ex ). u02 =
= 3x
so
1 + ex
(1 + ex )e3x
e + e2x

Z
ex
ex + 1
u2 (x) =
ex = ln(1 + ex ) ex . Hence
dx = ln
3x
2x
e +e
ex

u1 (x) =

y(x) = [c1 + ln(1 + ex )]ex + [c2 ex + ln(1 + ex )]e2x .

ex
ex
and
27. y1 = ex , y2 = ex and y1 y20 y2 y10 = 2. So u01 = , u02 =
2x
2x
Z x
Z x
e
e
dx + ex
dx. Hence the general solution is
yp (x) = ex
2x
2x

Z x
Z x
e
e
y(x) = c1
dx ex + c2 +
dx ex .
2x
2x